Penglihatan Binokular Pneumatologi: Kajian Socio-Historis Perspektif Mesopotamia dan Ibrani Kuno - Elia Singkoh; Milton Thorman Pardosi; Alvyn Cesarianto Hendriks (EPIGRAPHE (Jurnal Teologi dan Pelayanan Kristiani), 2022)
The Hebrew scriptures contain rich material on pneumatology. Cultural context greatly influenced the construction of dogmatics in biblical times, but the study of pneumatology from a social and historical point of view received less attention. This study aims to explore the social context of the meaning of spirits in the ancient Mesopotamian and Hebrew eras. Through a socio-historical approach, the pneumatology construction plot of the ancient Hebrews can be known, where its development also influences the construction of New Testament theology and can be used as a reference for the development of dogmatics at the end of time. Methods This research uses a qualitative descriptive approach. The mingling of the ancient Hebrews with the Mesopotamians influenced the ancient Hebrews' presuppositions for the articulation of pneumatology and its everyday use. The widespread and transcendental use of pneumatology occurred as a result of the initial conceptual fragility and articulation that developed from the Mesopotamians, thus influencing the perspective of ancient Hebrew pneumatology on daily implementation. The diversity of pneumatological articulations in ancient Hebrew literature is not a contradiction but a multiplicity of words that emerges from the socio-historical aspect.AbstrakKitab suci Ibrani berisi materi yang kaya tentang pneumatologi. Konteks budaya sangat mempengaruhi konstruksi dogmatika di zaman Alkitab, namun kajian pneumatologi dari sudut pandang sosial dan sejarah kurang mendapat perhatian. Penelitian ini bertujuan untuk mengeksplorasi konteks sosial pemaknaan roh di era Mesopotamia dan Ibrani kuno. Melalui pendekatan socio-historis, alur konstruksi pneumatologi bangsa Ibrani kuno dapat diketahui, di mana perkembangannya turut mempengaruhi konstruksi teologi Perjanjian Baru dan dapat dijadikan acuan pengembangan dogmatika di akhir zaman. Metode Penelitian ini menggunakan pendekatan kualitatif-deskriptif. Berbaurnya bangsa Ibrani kuno dengan bangsa Mesopotamia mempengaruhi presuposisi orang Ibrani kuno terhadap artikulasi pneumatologi serta penggunaannya sehari-hari. Penggunaan pneumatologi yang luas dan transcendental terjadi akibat rempuhan konseptual awal serta artikulasi yang berkembang dari bangsa Mesopotamia sehingga mempengaruhi perspektif pneumatologi orang Ibrani kuno terhadap implementasi sehari-hari. Diversitas artikulasi pneumatologi dalam literatur Ibrani kuno bukan merupakan kontradiksi melainkan multiplisitas kata yang mencuat dari aspek socio-historis.